The Effect of Capital Structure, Sales Growth and Liquidity on Performance with Company Size as Moderation - Apriliansyah; Eduard Ary Binsar Naibaho (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
This study aims to determine and test based on empirical evidence regarding the effect of Capital Structure, Sales Growth and Liquidity with firm size as moderation on Performance. Performance is measured by using Return on Asset. This study uses secondary data sources recorded in S&P Capital IQ. Four hundred ninety-five observations with purposive sampling technique in selecting samples from healthcare companies for Indonesia, Malaysia, Singapore, Thailand, the Philiphines, and Vietnam. For the period 2010 – 2020. The research method is a multiple linear regression model. The results show that Capital Structure and Sales Growth affect performance. This study also indicates that company size as a moderator variable has insignificance for capital structure and sales growth to performance. However, firm size affects the relationship between net liquidity and performance.